Struktur Sintaksis Anak Keterlambatan Berbicara (Speech Delay) Pascaterapi: Studi Kasus Caca - Syaravina, Siti Awal; Revita, Ike; Aslinda, Aslinda (Jurnal Ilmiah Global Education, 2025)
The problems discussed in this research is (1) how is the syntactic structure of speech delay children after therapy in Caca's case study? The purpose of this study is (1) to identify the syntactic structure of speech delay children after Caca's case study. This research uses a descriptive qualitative approach. In the data collection stage, direct interviews were conducted using the method of listening and speaking. The techniques used were fishing techniques with emotional and psychological approaches, tapping, recording and noting. At the data analysis stage, translational pairing was used to transliterate Caca's speech into Indonesian. Based on the results of data analysis, the syntactic structure produced by Caca can be seen in terms of aspects of syntactic categories, syntactic functions and semantic roles. Based on the syntactic category, Caca is able to master various word categories and shows the existence of morphosyntactic limitations such as affixation. Based on syntactic function, the sentence pattern is dominated by subject-predicate (SP) structure. Based on semantic role, Caca shows the dominance of the ability to structure the relationship between agent, action, subject and target in a simple way.